2023
DOI: 10.3390/ijms241914734
|View full text |Cite
|
Sign up to set email alerts
|

Pathomechanism of Pruritus in Psoriasis and Atopic Dermatitis: Novel Approaches, Similarities and Differences

Agnieszka Kaczmarska,
Dominika Kwiatkowska,
Katarzyna Konstancja Skrzypek
et al.

Abstract: Pruritus is defined as an unpleasant sensation that elicits a desire to scratch. Nearly a third of the world’s population may suffer from pruritus during their lifetime. This symptom is widely observed in numerous inflammatory skin diseases—e.g., approximately 70–90% of patients with psoriasis and almost every patient with atopic dermatitis suffer from pruritus. Although the pathogenesis of atopic dermatitis and psoriasis is different, the complex intricacies between several biochemical mediators, enzymes, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 156 publications
0
1
0
Order By: Relevance
“…JAKis seem to have better results in this area than TNF-α inhibitors or apremilast [76,103,104]. This could bring a valuable addition to psoriasis treatment, since for many patients, pruritus is the most bothersome manifestation of the disease [137].…”
Section: Discussionmentioning
confidence: 99%
“…JAKis seem to have better results in this area than TNF-α inhibitors or apremilast [76,103,104]. This could bring a valuable addition to psoriasis treatment, since for many patients, pruritus is the most bothersome manifestation of the disease [137].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, studies have demonstrated that IL-31 appears to contribute to the induction of pruritus in psoriasis. However, IL-31's relationship with pruritus intensity is not well established [30]. A study by Purzycka-Bohdan et al found substantially elevated levels of IL-31 in psoriasis patients compared to healthy controls, with 97.4% of psoriasis demonstrating pruritus.…”
Section: Discussionmentioning
confidence: 99%
“…1 Approximately 70%-90% of psoriasis patients and virtually all AD patients endure relentless itching, which not only exacerbates skin lesions but also affects mood, disrupts sleep patterns and impairs daily functioning. 2 Additionally, a subgroup of individuals with dermatological conditions, particularly those with AD, experience dysesthesia, manifesting as alloknesis (itch triggered by wearing clothes) or hyperknesis (exaggerated itching in response to typically itch-evoking stimuli). 3 Regrettably, pruritus often receives inadequate attention in patient care, despite its substantial burden on society.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic pruritus is frequently observed in various inflammatory dermatoses, notably conditions such as AD and psoriasis, as well as certain systemic or neurological diseases 1 . Approximately 70%–90% of psoriasis patients and virtually all AD patients endure relentless itching, which not only exacerbates skin lesions but also affects mood, disrupts sleep patterns and impairs daily functioning 2 . Additionally, a subgroup of individuals with dermatological conditions, particularly those with AD, experience dysesthesia, manifesting as alloknesis (itch triggered by wearing clothes) or hyperknesis (exaggerated itching in response to typically itch‐evoking stimuli) 3 .…”
Section: Introductionmentioning
confidence: 99%